Analisis Karakteristik Kolektor dan Proses Pembelian Batu Akik dengan Pendekatan Leisure Study - Sugeng Purwanto (Universitas Proklamasi 45 Yogyakarta, 2017)
The phenomenon of agate collectors into social behavior occurs in Indonesia, it is part of marketing in particular the purchase behavior of agate. This study aims to examine the findings about the characteristics of collectors with leisure study and how the purchasing process of agate in a qualitative research by case study method. The study is based on the concept of using four characteristics offered by Lee and Trace, namely casual collector, serious collector, social collector, and unique collector. Each characteristic will be analyzed in the pattern of social behavior in collecting agate, and how their behavior in the purchasing process of each character, represented by six informants selected through the selection of snowball samples. The results of the analysis show that the four characteristics of collectors have similar behavior in the buying process and to the perception of the aggregate value of the agile collection they seek, but the most important in the data finding is that collectors are part of different target markets than the general consumer.